Rating Methodology: New Look and New Horizons - Brusov, P.N.; Filatova, T.V.; Orekhova, N.P.; Kulik, V.L. (Journal of Reviews on Global Economics, 2018)
In the previous paper a new approach to rating methodology has been suggested. Key factors of a new approach were the following: 1) The adequate use of discounting of financial flows virtually not used in existing rating methodologies, 2) The incorporation of rating parameters (financial "ratios") into the perpetuity limit of modern theory of capital structure (Brusov-Filatova-Orekhova (BFO) theory): for companies with infinite lifetime. In current paper further development of a new approach has been done. We have generalized it for the general case of modern theory of capital structure (Brusov-Filatova-Orekhova (BFO) theory): for companies of arbitrary age. A serious modification of BFO theory in order to use it in rating procedure has been required. It allows to apply obtained results for real economics, where all companies have finite lifetime, introduce a factor of time into theory, estimate the creditworthiness of companies of arbitrary age (or arbitrary lifetime), introduce discounting of the financial flows, using the correct discount rate etc. This allows use the powerful tools of BFO theory in the rating. All these create a new base for rating methodologies.